Floral Volatiles: A Promising Method to Access the Rare Nocturnal and Crepuscular Bees - Martínez-Martínez, Carlos A.; Cordeiro, Guaraci D.; Martins, Herbeson O. J.; Kobal, Renan O. A. C.; Milet-Pinheiro, Paulo; Stanton, Mariana A.; Franco, Emanuella L.; Krug, Cristiane; Mateus, Sidnei; Schlindwein, Clemens; Dötterl, Stefan; Alves-dos-Santos, Isabel (Frontiers in Ecology and Evolution, 2021)
Crepuscular and/or nocturnal bees fly during the dusk, the dawn or part of the night. Due to their short foraging time and sampling bias towards diurnal bees, nocturnal bees are rarely collected and poorly studied. So far, they have been mostly sampled with light and Malaise traps. However, synthetic chemical compounds resembling floral volatiles were recently found to be a promising alternative to attract these bees. By reviewing available literature and collecting original data, we present information on the attraction and sampling of nocturnal bees with scent-baited traps. Bees were actively captured with entomological nets while approaching to filter papers moistened with distinct chemical compound, or passively caught in bottles with scent baits left during the night. So far, all data available are from the Neotropics. Nocturnal bees belonging to three genera, i.e. Ptiloglossa, Megalopta and Megommation were attracted to at least ten different synthetic compounds and mixtures thereof, identified from bouquets of flowers with nocturnal anthesis. Aromatic compounds, such as 2-phenyletanol, eugenol and methyl salicylate, and the monoterpenoid eucalyptol were the most successful in attracting nocturnal bees. We highlight the effectiveness of olfactory methods to survey crepuscular and nocturnal bees using chemical compounds typically reported as floral scent constituents, and the possibility to record olfactory preferences of each bee species to specific compounds. We suggest to include this method in apifauna surveys in order to improve our current knowledge on the diversity of nocturnal bees in different ecosystems.